Hard issues, soft solutions? A study on disaster risk, irregular migrants and the regulatory responses of the international community - Jonsson Blume,Fredrika (2024)
This thesis joins an emerging body of international legal scholarship that explores the ways in which international law can support disaster risk reduction. The focus of this thesis is on irregular migrants, ie migrants who do not comply with the immigration laws of their host state, and the specific vulnerability that they might experience in the context of disasters. Most legal scholars have thus far concentrated their efforts on identifying legally binding state obligations to reduce disaster risk, mainly on the basis of international human rights law. The argument presented in this thesis, however, is that the international human rights law framework does rather little to support disaster risk reduction, particularly in the case of irregular migrants. The thesis identifies two main issues in this regard, one being that there are yet few pronounced obligations on states to reduce disaster risk, the other being that irregular migrants are largely excluded from the human rights protection in any case. In light of the limitations of the international human rights law framework, the thesis sets out to explore the potential role of other international instruments. Notably, over the last couple of years, the international community has successfully produced a number of new instruments that in different ways touch upon the issues of disasters and/or migration. These are all soft law instruments, meaning that they do not impose any legally binding obligations on states. There is arguably reason to examine whether these instruments can support disaster risk reduction for irregular migrants – despite, or perhaps because of, their non-binding nature. The thesis provides a comprehensive overview of the soft law instruments of relevance to the issue at hand. Through a comparison with the human rights framework, it also elaborates on the main distinguishing features of the new soft law instruments. Drawing from these learnings, the thesis discusses what contribution these instruments can make in supporting disaster risk reduction for irregular migrants. Clearly, the new soft law instruments share some deficiencies with the international human rights law framework, but they also contain a range of innovative commitments and standards that, if implemented, could be of considerable use in reducing the disaster risk of irregular migrants. Despite their non-binding nature, the instruments have a potential to make an impact, both in terms of state compliance and more generally in terms of enhanced (international) engagement and cooperation on these issues. Given that the alternative would probably not be any hard law instruments, but rather no instruments at all, the thesis tentatively concludes that the recent growth of soft law instruments must be considered as a promising development – but also one which must be guarded against the dangers of back-sliding and inaction.
Keywords: disaster risk reduction; irregular migrants; international human rights law; soft law